Modelling unidirectional liquid spreading on slanted microposts - Cavalli, A; Blow, M; Yeomans, J (2013)
A lattice Boltzmann algorithm is used to simulate the slow spreading of drops on a surface patterned with slanted micro-posts. Gibb's pinning of the interface on the sides or top of the posts leads to unidirectional spreading over a wide range of contact angles and inclination angles of the posts. Regimes for spreading in no, one or two directions are identified, and shown to agree well with a two-dimensional theory proposed in Chu, Xiao and Wang. A more detailed numerical analysis of the contact line shapes allows us to understand deviations from the two dimensional model, and to identify the shapes of the pinned interfaces. © 2013 The Royal Society of Chemistry.